The Methodological Significance of Farabi's Scientific Heritage in Modern Educational, Scientific and Cultural Development Processes - Kenjayeva Dilrabo Rominovna (Scientific Trends, 2025)
This article examines the methodological significance of Abu Nasr al-Farabi’s scientific heritage in the context of modern educational, scientific and cultural development processes. The study analyzes Farabi’s epistemological principles, his classification of sciences, and the central role of logic in the formation of rational scientific thinking. Particular attention is given to Farabi’s pedagogical concepts, including the development of moral character, intellectual growth and the teacher–student relationship, which align with contemporary educational paradigms. The article also explores Farabi’s influence on interdisciplinary research methods, system-thinking approaches and cultural integration. It concludes that Farabi’s intellectual legacy offers enduring methodological value for addressing key challenges of modern education, scientific inquiry and intercultural dialogue.
Keywords: Farabi, scientific methods, history of science, philosophy, interdisciplinary approach.